Role of CD1a-restricted T cells in the immune responses to Staphylococcus aureus - Fu, X (2019)
CD1a has been demonstrated to contribute to anti-bacterial immune responses by presenting lipid antigens to T cells. Skin Staphylococcus aureus (S. aureus) colonization has been documented to be strongly associated with the severity of skin inflammatory diseases including atopic dermatitis (AD). However, there have been limited studies of how the bacterial colonization contributes to pathology and exacerbation of disease.